Enhanced Thermo‐Mechanical Stiffness, Thermal Stability, and Fire Retardant Performance of Surface‐Modified 2D MoS2 Nanosheet‐Reinforced Polyurethane Composites. Issue 1 (15th January 2019) - Malkappa, Kuruma; Ray, Suprakas Sinha; Kumar, Neeraj
Abstract : Inside Front Cover : The work in1800562 by Suprakas Sinha Ray and coworkers, reports the development of new‐generation polyurethane composite materials containing surface‐modified MoS2 nanosheets. The composite shows a 65% higher storage modulus and significantly improved thermal stability than that of pure polymers. Moreover, the composite shows improved fire retardation properties, with a 45% and 67.5% decrease in the peak heat and total heat release rates, respectively, as compared with those of pure polymers.